APAKAH LEMBAGA PENDIDIKAN PEDULI DENGAN PELAYANAN? - Samuel PD Anantadjaya; Widya Granita; Irma M Nawangwulan; Fitriyah Nurhidayah; Nuria Astagini (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract: With the growing numbers of educational institutions, both formal, informaland informal, and with the improving comprehension of the society on the importanceof service, this research aims to investigate the level of satisfaction of students of thoseeducational institutions. This is also in conformation with the expansion of informationtechnology whereby the information exchanges are faster, and educational institutions,which disregard this trend may be left behind. Using the basic foundation from the fieldof study on consumer behavior, this research tries to evaluate on service delivery andperformance of educational institutions. This research relies on purposive andproportional sampling to university students in Jakarta, Tangerang, and Bandung.Interview sessions, observations, and questionnaire distributions are conducted togather primary data from the registered students of selected formal educationalinstitutions. Of course, it is expected that personnels of those educational institutionsgrasp the important role of service delivery and performance, and the influential factorson the success of services. Nevertheless, the findings show that the level of servicedelivery of lecturers and administrative staff in higher educational institutions needdrastic improvement to allow students to receive the optimal level of service.Keywords: consumer behavior, formal educational institution, service factors